2019
DOI: 10.1097/mao.0000000000002170
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Residual Hearing After Cochlear Implant Surgery With Deep Insertion Electrode Arrays

Abstract: Objective: To evaluate the hearing preservation (HP) in cochlear implant (CI) recipients who did not fulfill the criteria for electric acoustic stimulation (EAS). Study Design: Prospective study Setting: Tertiary academic hospital. Patients: Adults undergoing CI with deep insertion electrode arrays who had measurable residual hearing (RH) before surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
1
11
0
2
Order By: Relevance
“…In contrast to this belief, Manjaly et al 27 in 2018 reported on complete hearing preservation with full insertion of FLEX 28 electrode array in patients with pre-operative hearing 85 dB HL at 250 Hz. Sierra et al 28 in 2019 reported on complete/partial hearing preservation using both FLEX SOFT (array length 31.5 mm), STANDARD (array length 31.5 mm) and FLEX 28 (array length 28 mm) electrode in majority of the cases. All these electrodes are capable of going beyond the basal turn of the cochlea is an indirect proof that the electrode array did not cause any intracochlear structural damage.…”
Section: Implications Of Choosing Electrode Array Matching the Cochle...mentioning
confidence: 99%
“…In contrast to this belief, Manjaly et al 27 in 2018 reported on complete hearing preservation with full insertion of FLEX 28 electrode array in patients with pre-operative hearing 85 dB HL at 250 Hz. Sierra et al 28 in 2019 reported on complete/partial hearing preservation using both FLEX SOFT (array length 31.5 mm), STANDARD (array length 31.5 mm) and FLEX 28 (array length 28 mm) electrode in majority of the cases. All these electrodes are capable of going beyond the basal turn of the cochlea is an indirect proof that the electrode array did not cause any intracochlear structural damage.…”
Section: Implications Of Choosing Electrode Array Matching the Cochle...mentioning
confidence: 99%
“…LWEs. There is another report of complete hearing preservation in nine out 25 patients (35%) with LWEs of different lengths after 1 year[46].…”
mentioning
confidence: 94%
“…1 is the main outcome variable. Based on three studies in literature (35)(36)(37) we expect a large range of hearing preservation for each group, from 0 (no preservation, i.e., loss of all hearing) to 100 (full preservation, hearing stable), and occasionally above (improved hearing). These three studies showed means of 56, 74, and 53, respectively and within-group standard deviations, σ W, of 37, 19 and 37.…”
Section: Sample Size {14}mentioning
confidence: 99%